Socialization And Education Of Patient Safety Goals For Nurses At Melati General Hospital Perbaungan - Sontina Saragih (Pusat Riset dan Inovasi Nasional, 2024)
Patient safety is a global health concern, with the primary objective of preventing harm to patients and addressing unavoidable side effects. Key patient safety goals include effective patient assistance, clear communication, safe medication practices, ensuring accurate procedures and patient identification, minimizing infection risks, and reducing the likelihood of injury from falls. The Service Team at Melati General Hospital implemented a method to socialize these safety goals to nurses through lectures and interactive Q&A sessions. The results indicated a significant improvement in nurses' knowledge about patient safety goals, with a post-test increase to 94%. This enhanced understanding is expected to be applied in patient care, such as accurate patient identification, adherence to the five moments of hand hygiene, and further minimizing injury risks, thereby improving overall service quality.